(untitled) (Santa Barbara, Calif.)
America loves sports. This book examines and details the proof of this fascination seen throughout American society―in our literature, film, and music; our clothing and food; and the iconography of the nation.
Keywords: Vận động viên,Thể thao,Sports,Athletes; Lịch sử,Lịch sử,History,History; Hoa Kỳ,Hoa Kỳ,United States,United States